Mammography screening is associated with more favorable breast cancer tumor characteristics and better overall survival: Case-only analysis of 3,739 Asian breast cancer patients. - Hartman, Mikael (LIPPINCOTT WILLIAMS & WILKINS, 2023)
Annual Meeting of the American-Society-of-Clinical-Oncology (ASCO)